THE DIGNITY AND THE CURSE OF THE SPORT - D. Jovanović, Milan (Scientific Journal Management in Sports, 2015)
The following text reviews in discussion the ethical and axiological aspects of sports, as every other global phenomenon in the modern world that has its own professionalism, and as an opposition has also its curse. In the first part of this work the components that enable the athletes and other people involved in sports will be analyzed on the way to achieve dignity in life as one of the biggest values in the process of finding the meaning of life. The second part of the work focuses on the modes of sports concept "curses" that could disturb or unable creation of positive attitude toward meaning of life, among athletes and other participants in sport.